Kontekstualitas Islam Tentang Identitas Gender Waria - Nur Kholis (Esensia: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
This article aims to find out the answer of gender identity polemic of transsexual in Islamic thought. Therefore, tracking the foundation of Islamic thought in the Qur’an about transsexual’s gender identification is required due to the fact that someone’s Islamic attitude is always determined by one’s interpretation. The results found indicated that the Islamic contextuality of transsexual’s gender identity can be propped on QV. Al-Hajj [22]: 5 and QV. Al-Nur [24]: 31. From those two verses, it is understood that: (1) The transsexual phenomenon is “natural reality” as imperfect created beings since in the form of a fetus (mudlghah ghairi mukhallaqah); (2) The transsexual are exception for women to cover her aurat, because of the condition as men who do not have sexual desire on women (ghairi uli al-irbat min al-rijal). This conclusion is validated from the meaning of the hadith of the Prophet who cursed transvestites as intentional behavior (bi al-qashdi/ bi takalluf), not because of the nature that cannot be avoided (bi al-khalq/ min ashl al-khilqat). In the circumstances of this kind mukhannats khalqi, the existance of transsexual’s gender identity is not cursed and even received in Islam.